Pengaruh Pemupukan Kalium Terhadap Aktivitas Stomata Dan Ketahanan Kekeringan - Ivonne Fitri Mariay (Fakultas Pertanian Universitas Papua, 2012)
This objective of the study is to determine the effect of potassium nutrition on stomatal aperture and drought resistance. Research has been conducted in the greenhouse of the Faculty of Agriculture, Gadjah Mada University in March-May 2012. This experiment was arranged on Factorial Completely Randomized Design (RAKL). The first factor was KCl consist of three level thoose are 0 kg ha-1, 50 kg ha-1, and 100 kg ha-1. The second factor was water consist of four levels which wereenough water and less water. Parameters observed were periodic observations on plant height while the observations made at the first harvest and the end covers root dry weight, shoot dry weight, total dry weight, leaf area, stomatal aperture and proline compound content. The results showed that potassium fertilization affect proline levels in maize, proline accumulation also significantly affected by water deficit conditions. The relationship between stomatal aperture width is closely related to water stress conditions that can increase the accumulation of proline.